RESPONSE TIME AND RECOVERY TIME OF A SEMICONDUCTOR SENSOR FOR DETECTING METHANE AND NATURAL GAS - Khodieva Nargiza Djurakulovna; Eshkobilova Mavjuda Ergashboyevna (Research Focus International Scientific Journal, 2025)
The response and recovery times of gas sensors provide insights into their dynamic behavior and are determined through experimental methods. The response time refers to the period needed for the sensor to reach 90% of its final signal value after exposure to a sudden change in gas concentration. This is often labeled as τ₀₉ or τ_response. Conversely, the recovery time, denoted as τ₀₁ or τ_recovery, is the time taken for the sensor to return to 10% of its initial baseline value after the gas is removed and clean air is introduced.